An effective pathway for 5‐brominemethylfurfural synthesis from biomass sugars in deep eutectic solvent. Issue 12 (29th May 2017) - Le, Kai; Zuo, Miao; Song, Xiaoqiang; Zeng, Xianhai; Tang, Xing; Sun, Yong; Lei, Tingzhou; Lin, Lu
Abstract: BACKGROUND: As a novel platform molecule, 5‐bromomethylfurfural (5‐BMF) has great potential in the production of varieties of value added chemicals as well as biofuels. RESULT: To overcome the toxicity of the previous 5‐BMF preparation process and environment issues, a brand new 5‐BMF synthesis pathway is presented in this study. In a biphasic deep eutectic solvent (DES)/MIBK reaction system, reactants and catalysts are enriched in the DES phase and the 5‐BMF produced is continuously in situ extracted to the organic solvent phase, giving a 5‐BMF yield of up to 50%(mass yield)from fructose. This biphasic reaction system for 5‐BMF synthesis has the advantages of green processing and solvent recyclability. CONCLUSION: This research may provide a new alternative for the production of platform chemicals and enriches the map of bio refinery concept. © 2017 Society of Chemical Industry